Comparative antimalarial, toxicity and mito-protective effects of Diospyros mespiliformis Hochst. ex A. DC. and Mondia whitei (Hook.f.) Skeels on Plasmodium berghei infection in mice. (25th March 2021) - Olanlokun, John Oludele; Bodede, Olusola; Prinsloo, Gerhard; Olorunsogo, Olufunso Olabode
Abstract: Ethnopharmacological relevance: Diospyros mespiliformis Hochst. ex A. DC. and Mondia whitei (Hook.f.) Skeels are traditionally used in Africa for the treatment of malaria. However, scientific evidence to substantiate this folkloric claim and their effects on liver mitochondria during malaria treatment have not been reported. Aim of the study: This study investigated the efficacy of D. mespiliformis and M. whitei against chloroquine-sensitive and resistant strains of malarial parasites in mice. It also investigated the toxicity and protection against cellular organelles like mitochondria. Materials and methods: Male Swiss mice were infected with a chloroquine resistant (ANKA) strain of Plasmodium berghei and were treated via oral gavage with methanol extracts of D. mespiliformis and M. whitei reconstituted in diluted dimethylsulfoxide as vehicle (DMSO, 5% v/v) for five consecutive days. Percentage parasite load and clearance were assessed by microscopy. The infected control was treated with the vehicle. Hematological indices were assessed using standard procedures. Alanine aminotransferase (ALT), aspartate aminotransferase (AST) and alkaline phosphatase (ALP) were determined using assay kits. Hepatic mitochondria were isolated via centrifugation, and their permeability transition (mPT), ATPase (mATPase) activity and lipid peroxidation (mLPO) were determined spectroscopically. Liver tissue histology was carried out by standard laboratory procedures. Phytochemical analysis of both extracts were performed using LC-MS to identify the most prominent compounds from each of the extracts. Results: After treatment on day 5, D. mespiliformis and M. whitei at 400 mg/kg decreased mean values for: percentage parasitemia (5.0 ± 1.0, 2.0 ± 0.2), increased Packed Cell Volume (PCV) (36.0 ± 1.4, 36.0 ± 0.0%) and platelets (2.0 ± 1.4, 2.0 ± 2.8 × 10 5 mm 3 ) relative to the untreated control (20.0 ± 5.2; 30.0 ± 0.0%; 1.4 ± 1.4 × 10 5 mm 3, respectively). At the same dose, D. mespiliformis and M. whitei decreased ALT (8.0 ± 3.8, 24.2 ± 4.0U/L), AST (6.2 ± 0.8, 8.0 ± 0.9U/L) and ALP (56.0 ± 0.7, 51.0 ± 1.0U/L) activities compared to the infected control (77.0 ± 10.9U/L, 14.0 ± 0.7U/L and 76.0 ± 6.0U/L, respectively). Both D. mespiliformis and M. whitei reversed mPT opening, decreased mATPase enhancement and mLPO, relative to the control. Histopathology of the liver showed extensive hemorrhagic lesions and severe disseminated congestion in the infected control while both D. mespiliformis and M. whitei were well tolerated at the highest dose. The LC-MS analysis of D. mespiliformis showed the presence of betulinic acid, tocopherol and kaempferol with antimalarial and antioxidant properties while the M. whitei sample contained coumarin and chlorogenic acid that have antimalarial and hepato-protective properties. Conclusions: D . mespiliformis and M. whitei show antimalarial effects against resistant Plasmodium berghei infection, enhanced cell viability, mito-protection and are not toxic in mice. Graphical abstract: Image 1